Killing for purposes other than slaughter: poultry. (13th November 2019) - ,; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Depner, Klaus; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, Jose Luis; Gortázar Schmidt, Christian; Miranda Chueca, Miguel Ángel; Roberts, Helen Clare; et al.
Abstract: Poultry of different ages may have to be killed on‐farm for purposes other than slaughter (in which slaughtering is defined as being for human consumption) either individually or on a large scale (e.g. because unproductive, for disease control, etc.). The processes of on‐farm killing that were assessed are handling and stunning and/or killing methods (including restraint). The latter were grouped into four categories: electrical methods, modified atmosphere, mechanical methods and lethal injection. In total, 29 hazards were identified and characterised, most of these regard stunning and/or killing. Staff were identified as origin for 26 hazards and 24 hazards were attributed to lack of appropriate skill sets needed to perform tasks or due to fatigue. Specific hazards were identified for day‐old chicks killed via maceration. Corrective and preventive measures were assessed: measures to correct hazards were identified for 13 hazards, and management showed to have a crucial role in prevention. Eight welfare consequences, the birds can be exposed to during on‐farm killing, were identified: not dead, consciousness, heat stress, cold stress, pain, fear, distress and respiratory distress. Welfare consequences and relevant animal‐based measures were described. Outcome tables linking hazards, welfare consequences, animal‐based measures, origins, preventive and corrective measures were developed for each process. Mitigation measures to minimise welfare consequences were also proposed.